Artificial intelligence and challenges for copyright law. (10th April 2021) - Kariyawasam, Kanchana
Abstract: The question of who should own the copyright of a creative work by an artificial intelligence (Al) is as yet largely unanswered. Due to the author's increased distance from the works being created, the granting of copyright protection to AI has not been forthcoming. This article assesses the prevalence of AI- and computer-generated works in which, beyond the initial input, the works produced involve more artificial than human contribution, and the impact this has on authorship. While the main geographical focus of this article is Australia, it makes comparisons with the UK and New Zealand (NZ) to explore how Australian copyright law can be adapted to incorporate positive aspects of UK and NZ law. This article explains how the statutory provisions in both the UK and NZ are undeniably far-sighted in the modern world, in which computer-generated programmes are increasingly used. This article argues that the case-by-case basis is most suitable when deciding the human entity who is the fortunate receiver of copyright protection in works that are essentially made by an advanced non-human entity.